Streptococcus suis contributes to inguinal lymph node lesions in piglets after highly pathogenic porcine reproductive and respiratory syndrome virus infection - Wang, Shujie; Xu, Min; Yang, Kongbin; Zhang, Ying; Li, Siqi; Tang, Yan-Dong; Wang, Jinliang; Leng, Chaoliang; An, Tongqing; Cai, Xuehui (Frontiers in Microbiology, 2023)
The swine pathogens porcine reproductive and respiratory syndrome virus (PRRSV) and Streptococcus suis have both been reported to cause damage to the immune organs. Inguinal lymph node (ILN) injury has been reported in PRRSV-infected pigs with secondary S. suis infection, but not much is known about the mechanism. In this study, secondary S. suis infection after highly pathogenic (HP)-PRRSV infection caused more severe clinical symptoms, mortality and ILN lesions. Histopathological lesions were seen in ILNs with a marked decrease in lymphocyte numbers. Terminal deoxynucleotidyl transferase (TdT)-mediated de-oxyuridine triphosphate (dUTP)-biotin nick end-labeling (TUNEL) assays revealed that HP-PRRSV strain HuN4 alone induced ILN apoptosis, but dual-infection with S. suis strain BM0806 induced greater levels of apoptosis. Besides, we found that some HP-PRRSV-infected cells underwent apoptosis. Furthermore, anti-caspase-3 antibody staining confirmed that ILN apoptosis was mainly induced by a caspase-dependent pathway. Pyroptosis was also observed in HP-PRRSV-infected cells, and there was more pyroptosis in piglets infected with HP-PRRSV alone compared with those with secondary S. suis infection, and HP-PRRSV-infected cells underwent pyroptosis. Altogether, this is the first report to identify pyroptosis in ILNs and which signaling pathway is related to ILN apoptosis in single or dual-infected piglets. These results contribute to a better understanding of the pathogenic mechanisms during secondary S. suis infection.